2021
DOI: 10.1080/1744666x.2021.1908128
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Tocilizumab in severe and critical COVID-19: A Systematic Review and Meta-Analysis

Abstract: Objectives Currently published papers and clinical guidelines regarding the effects of tocilizumab in severe and critical COVID-19 are contradictory. The aim of this meta-analysis was to combine the results of clinical studies of different designs to investigate the efficacy and safety of tocilizumab in severely-to-critically ill COVID-19 patients. Methods A systematic search was performed in PubMed, Embase, CENTRAL, ClinicalTrials.gov, Scopus, and preprint servers up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 82 publications
6
32
0
2
Order By: Relevance
“…In one randomized control study comparing tocilizumab with usual care in non ICU COVID-19 patients with moderate to severe pneumonia, there was also no difference in mortality at 28-days (10). Similarly, a recent meta-analysis in ICU patients found no signi cant difference in mortality rates between the tocilizumab group and the comparator groups (24). Alternatively, a previous retrospective cohort study in ICU COVID-19 patients found signi cantly lower ICU mortality in the tocilizumab group but no difference in the 28-day mortality (23).…”
Section: Discussionmentioning
confidence: 96%
“…In one randomized control study comparing tocilizumab with usual care in non ICU COVID-19 patients with moderate to severe pneumonia, there was also no difference in mortality at 28-days (10). Similarly, a recent meta-analysis in ICU patients found no signi cant difference in mortality rates between the tocilizumab group and the comparator groups (24). Alternatively, a previous retrospective cohort study in ICU COVID-19 patients found signi cantly lower ICU mortality in the tocilizumab group but no difference in the 28-day mortality (23).…”
Section: Discussionmentioning
confidence: 96%
“…Other RCTs also reported no mortality bene ts in patients who received multiple doses of tocilizumab than standard therapy [6], [14]Contrary to that, two large RCTs using one or more tocilizumab doses in critically ill patients with COVID-19 reported improved survival [13], [16], [18], and an increase in the duration of organ support-free days [16]. Moreover, A systemic review and meta-analysis found that tocilizumab use in critically ill patients with COVID-19 reduces mortality and improves patients' outcomes [3]. However, the exact number of patients who received single versus multiple doses was not clearly stated in any previous studies mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact number of patients who received single versus multiple doses was not clearly stated in any previous studies mentioned. Also, none of these studies compared the mortality bene ts between various tocilizumab regimens [3], [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations